Characterization of a Novel Bacteriophage Henu2 and Evaluation of the Synergistic Antibacterial Activity of Phage-Antibiotics - Xianghui Li; Tongxin Hu; Jiacun Wei; Yuhua He; Abualgasim Elgaili Abdalla; Guoying Wang; Yanzhang Li; Tieshan Teng (MDPI AG, 2021)
Staphylococcus aureus phage Henu2 was isolated from a sewage sample collected in Kaifeng, China, in 2017. In this study, Henu2, a linear double-stranded DNA virus, was sequenced and found to be 43,513 bp long with 35% G + C content and 63 putative open reading frames (ORFs). Phage Henu2 belongs to the family Siphoviridae and possesses an isometric head (63 nm in diameter). The latent time and burst size of Henu2 were approximately 20 min and 7.8 plaque forming unit (PFU)/infected cells. The Henu2 maintained infectivity over a wide range of temperature (10-60 °C) and pH values (4-12). Phylogenetic and comparative genomic analyses indicate that Staphylococcus aureus phage Henu2 should be a new member of the family of Siphoviridae class-II. In this paper, Phage Henu2 alone exhibited weak inhibitory activity on the growth of S. aureus. However, the combination of phage Henu2 and some antibiotics or oxides could effectively inhibit the growth of S. aureus, with a decrease of more than three logs within 24 h in vitro. These results provide useful information that phage Henu2 can be combined with antibiotics to increase the production of phage Henu2 and thus enhance the efficacy of bacterial killing.